Alfred Howe Terry correspondence and journal - Terry, Alfred Howe, 1827-1890.
Journal (1876 May 17-August 22) of Terry's expedition from Fort Abraham Lincoln, Dakota Territory, to the Bighorn-Powder River region of Montana, giving information on Gen. George A. Custer and the Battle of the Little Big Horn, as well as on troop movements and routine military matters. The journal also contains miscellaneous notes, lists, sketches, and mathematical figuring. Includes a letter (1875 March 17) from Terry to Gen. C.A. Carleton.
Microfilm edition available
Microfilm produced from originals in the Manuscript Division.
Army officer.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Carleton, C. A. -- 1836-1897 -- Correspondence; Custer, George A. -- 1839-1876.; United States. -- Army -- Military life; Fortification -- North Dakota; Little Bighorn, Battle of the, Mont., 1876.; Military bases -- North Dakota; Bighorn River (Wyo. and Mont.); Fort Abraham Lincoln (N.D.); Montana -- History, Military; Powder River (Wyo. and Mont.); West (U.S.) -- History, Military; Army officers